Masses of ground-state mesons and baryons, including those with heavy quarks - Yin, Pei-Lin; Chen, Chen [UNESP]; Krein, Gastao [UNESP]; Roberts, Craig D.; Segovia, Jorge; Xu, Shu-Sheng (Amer Physical Soc, 2019)
Using a confining, symmetry-preserving regularization of a vector x vector contact interaction, we compute the spectra of ground-state pseudoscalar and vector of (f (g) over bar) mesons, scalar and axial-vector (fg) diquarks, and J(P) = 1/2(+), 3/2(+) (fgh) baryons, where f, g, h is an element of {u, d, s, c, b}. The diquark correlations are essentially dynamical and play a key role in formulating and solving the three-valence-quark baryon problems. The baryon spectrum obtained from this largely algebraic approach reproduces the 22 known experimental masses with an accuracy of 2.9(2.4)%. It also possesses the richness of states typical of constituent-quark models, predicting many heavy-quark baryons not yet observed. This study indicates that diquark correlations are an important component of all baryons; and owing to the dynamical character of the diquarks, it is typically the lightest allowed diquark correlation that defines the most important component of a baryon's Faddeev amplitude.